Retinopathy of prematurity: Improving parental awareness and perceived importance of follow-up eye exams using an informative pamphlet (Interim Report). Issue 5 (October 2016) - Daftarian, Soheil; Lin, Pamela; Mitchell, Kelly
Abstract: Background: Treatment of retinopathy of prematurity (ROP) to prevent blindness depends on timely eye exams of at-risk infants. Purpose: To examine the effectiveness of a user-friendly pamphlet in improving parents' perceived importance of and ultimate adherence to ROP screening guidelines. Methods: A pamphlet on ROP was provided to parents of at-risk infants. Before and after reading the pamphlet, the parents were evaluated on their knowledge of ROP and their perception of the importance of timely follow-up screening. Results: Before and after pamphlet exposure, the knowledge of ROP essentially stayed the same for all parents. Before pamphlet exposure, a couple of parents chose lower than "Extremely Important" for perceived importance of follow-up eye exams. After pamphlet exposure, all parents chose "Extremely Important" for importance of follow-up. Conclusion: Providing a user-friendly pamphlet on ROP to parents of preterm infants could increase the perceived importance of timely follow-up eye exams, thus reducing the rate of potentially preventable blindness.